Bioactive triterpenoids from the caffeine-rich plants guayusa and maté. (January 2019) - Chianese, G.; Golin-Pacheco, S.D.; Taglialatela-Scafati, O.; Collado, J.A.; Munoz, E.; Appendino, G.; Pollastro, F.
Abstract: Unlike all other caffeinated plants, guayusa ( Ilex guayusa Loes.) and maté ( Ilex paraguariensis A. St. Hill) contain high amounts of pentacyclic triterpenoid acids and alcohols. A phytochemical investigation on these plants revealed a similar triterpenoid profile and a content of ursolic acid (0.7–1%) and amyrin esters (up to 0.5%), quite unusual for dietary plants. The major constituent of the amyrin complex from both plants is α-amyrin palmitate (2a ), accompanied by lower amounts of its corresponding palmitoleate (2b ) and by the corresponding constitutional isomers from the β-series (3a and 3b, respectively). Ursolic acid (1 ) was identified as the responsible for the activity of maté and guayusa extracts in the activation of TGR5, a nuclear receptor of relevance for the prevention and management of diabetes and metabolic syndrome because of its involvement in the regulation of energy expenditure and insulin sensitivity. Graphical abstract: Unlabelled Image Highlights: Guayusa is growingly popular as a caffeinated beverage, similar to maté. The phytochemistry and bioactivity of guayusa are still substantially unexplored. Guayusa and maté extracts activate TGR5, a transcription factor involved in diabetes. Ursolic acid is the active constituent from both plants. The amyrin complex (α/β-amyrin palmitate and palmitoleate) is inactive on TGR5.